The Kerry Babies, criminology, and Reinhart Koselleck - Molloy, Ciara (Criminology & criminal justice, 2025)
The Kerry Babies case was a criminal investigation that followed the discovery of a dead infant on a beach in the southwest of Ireland in April 1984. Charges were laid and dismissed. A tribunal of inquiry into alleged police malpractice followed, and the case returned to the courts 35 years later. This paper takes a multidimensional approach to historical time, drawing on the works of German philosopher Reinhart Koselleck to analyse the case, its legacy, and its implications for criminological theory. A Koselleckian approach – drawing in particular on the role of anachronisms, the mobilisation of memory and the categories of experience and expectation – facilitates a novel perspective on child killing, unmarried motherhood, and policing in 20th-century Ireland.